2000
DOI: 10.1038/sj.bjp.0703287
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of arterial intimal hyperplasia by cilostamide, a cyclic nucleotide phosphodiesterase 3 inhibitor, in a rat balloon double‐injury model

Abstract: 1 The eects of cilostamide, a cyclic nucleotide phosphodiesterase 3 (PDE3) selective inhibitor, on vascular intimal hyperplasia were evaluated using a single-balloon injury model and a double-injury model in which the rat common carotid artery was subjected to a second injury at a site injured 14 days previously. 2 In the double-injury model, the second balloon injury caused more severe intimal hyperplasia (intima/media (IM) ratio, 1.88+0.10) than in the single-injury model (1.09+0.08). Histopathological study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Synergistic effects of PDE3 and PDE4 inhibitors have been documented previously in several cell-or tissue-based functional assays, including relaxation of smooth muscle strips (41)(42)(43), attenuation of vascular smooth muscle cell proliferation (39,44), stimulation of vascular smooth muscle cell migration (45), induction of apoptosis in leukemic cells (44,46), attenuation of T-lymphocyte proliferation (47,48), and inhibition of T-lymphocyte interleukin-2 synthesis (47). In mice injected with T-cell mitogens, PDE3 and PDE4 inhibitors also act synergistically in vivo to attenuate systemic tumor necrosis factor-␣ release and protect against liver injury (49).…”
Section: Discussionmentioning
confidence: 65%
“…Synergistic effects of PDE3 and PDE4 inhibitors have been documented previously in several cell-or tissue-based functional assays, including relaxation of smooth muscle strips (41)(42)(43), attenuation of vascular smooth muscle cell proliferation (39,44), stimulation of vascular smooth muscle cell migration (45), induction of apoptosis in leukemic cells (44,46), attenuation of T-lymphocyte proliferation (47,48), and inhibition of T-lymphocyte interleukin-2 synthesis (47). In mice injected with T-cell mitogens, PDE3 and PDE4 inhibitors also act synergistically in vivo to attenuate systemic tumor necrosis factor-␣ release and protect against liver injury (49).…”
Section: Discussionmentioning
confidence: 65%
“…Inhibition of PDE3 has also been shown to mediate the inhibitory effect of NO in VSMC mitogenesis, 22 and the PDE3 inhibitor cilostamide suppressed arterial intimal hyperplasia in a rat balloon injury model. 29 Given that NO is an important antiatherogenic molecule in vivo, inhibition of PDE3 activity with PDE3-selective inhibitors may be an effective antiatherogenic strategy. It has already been shown that the PDE3 inhibitor cilostazol (an analogue of cilostamide) is an effective drug for the clinical treatment of symptoms of intermittent claudication due to peripheral arterial disease, which itself, is believed to be a manifestation of systemic atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cilostazol, a structural analog of the PDE3 inhibitor used in our studies (cilostamide), has been considered a promising candidate drug for prevention of restenosis because of its vascular and platelet effects (Ochiai et al, 1999;Tanabe et al, 2001). Indeed, several studies have indicated some degree of success in suppressing neointimal formation in animal models using cilostazol (Inoue et al, 2000;Aoki et al, 2001). Results of trials in which both aspirin and cilostazol were delivered in combination after stenting showed results comparable to those obtained when aspirin and ticlopidine, an inhibitor of platelet aggregation, were used .…”
Section: Human Aortic Contractile and Synthetic Vsmc Express Differenmentioning
confidence: 99%